Kajian Penulisan Aksara Bali pada Papan Nama Akomodasi Pariwisata Berbahasa Asing di Kawasan Wisata Kuta: Study of Balinese Script Writing on Foreign Language Tourist Accommodation Signs in the Kuta Tourist Area - Widianingsih, Desak Made Dian; Wisnu, I Wayan Gede; Aryana, I. B. Putra Manik (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
The discovery of errors in writing Balinese script on tourist accommodation nameplates, especially those from foreign languages, has caused a lack of Balinese script observers to realize the existence of writing rules in the Balinese script installation guidebook, which continues to be updated. This study aimed to see and prove the existence of Balinese scriptwriting, which still has errors. The subjects of this study were Balinese script tourist accommodation nameplates using foreign languages ??in the Kuta tourist area. The object of this study was the Balinese script writing on nameplates of foreign language tourist accommodation. This study used a qualitative descriptive research method. The research methods used were observation, documentation, and interviews. This study's results used several analyses, including data identification, reduction, and classification. The results of this study describe (1) The existence of Balinese script writing on tourist accommodation nameplates by the enactment of new regulations from the government in the form of Balinese script installation guidelines from Pasamuhan Agung VIII in 2023 which were taken based on each highway in the Kuta area, especially the tourist area with the results of 36 nameplate data. (2) The results of the data on errors in the form of writing Balinese script on the nameplates are divided into errors in writing Balinese script words, errors in writing the ancient script, errors in writing Balinese numbers, and technical errors and regulations for writing Balinese script on nameplates, nine errors were obtained. The results of the interview stated the conditions of the Balinese people in following government regulations in writing Balinese script on nameplates, especially for tourism accommodation in the Kuta tourist area, as well as the problems that cause errors in writing Balinese script.